Chemical Composition and Antimicrobial Properties of Mentha × piperita cv. ‘Kristinka’ Essential Oil - Ippolito Camele; Daniela Gruľová; Hazem S. Elshafie (Plants, 2021)
Several economically important crops, fruits and vegetables are susceptible to infection by pathogenic fungi and/or bacteria postharvest or in field. Recently, plant essential oils (EOs) extracted from different medicinal and officinal plants have had promising antimicrobial effects against phytopathogens. In the present study, the potential microbicide activity of Mentha × piperita cv. ‘Kristinka’ (peppermint) EO and its main constituents have been evaluated against some common phytopathogens. In addition, the cell membrane permeability of the tested fungi and the minimum fungicidal concentrations were measured. The antifungal activity was tested against the following postharvest fungi: Botrytis cinerea, Monilinia fructicola, Penicillium expansum and Aspergillus niger, whereas antibacterial activity was evaluated against Clavibacter michiganensis, Xanthomonas campestris, Pseudomonas savastanoi and P. syringae pv. phaseolicola. The chemical analysis has been carried out using GC-MS and the main components were identified as menthol (70.08%) and menthone (14.49%) followed by limonene (4.32%), menthyl acetate (3.76%) and β-caryophyllene (2.96%). The results show that the tested EO has promising antifungal activity against all tested fungi, whereas they demonstrated only a moderate antibacterial effect against some of the tested bacteria.